2012
DOI: 10.1097/wno.0b013e31823a9ebc
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Visual Acuity and Automated Perimetry Findings in Patients With Neuromyelitis Optica or Multiple Sclerosis After Single or Multiple Attacks of Optic Neuritis

Abstract: Visual outcome was significantly worse in NMO than in MS. After a single episode of ON, suspicion of NMO should be raised in the presence of severe residual VF deficit with automated perimetry and lowered in the case of complete VF recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 19 publications
3
41
0
5
Order By: Relevance
“…For ON, these include patients with severe vision loss (<20/200) or visual field depression, poor visual recovery, severe and diffuse peripapillary retinal nerve fiber layer loss, and MRI findings of posterior optic nerve or chiasm involvement of extensive visual pathway lesions (1117). For TM, the presence of a longitudinally extensive spinal cord lesion or central cord involvement should raise suspicion for NMO.…”
Section: Neuromyelitis Optica Diagnosismentioning
confidence: 99%
“…For ON, these include patients with severe vision loss (<20/200) or visual field depression, poor visual recovery, severe and diffuse peripapillary retinal nerve fiber layer loss, and MRI findings of posterior optic nerve or chiasm involvement of extensive visual pathway lesions (1117). For TM, the presence of a longitudinally extensive spinal cord lesion or central cord involvement should raise suspicion for NMO.…”
Section: Neuromyelitis Optica Diagnosismentioning
confidence: 99%
“…However, standard high-contrast visual acuity measurements were also significantly worse in NMO-ON eyes relative to the other groups, and there was no significant difference among groups in RNFL thickness in non-ON eyes. A recent study (20) compared the results of automated perimetry in patients with NMO-related ON and MS-related ON and found that visual field mean deviation was significantly greater in the NMO-ON eyes than in the MS-ON eyes. Therefore, OCT in this setting may simply be another marker of incomplete visual recovery after ON, and it is unclear whether OCT measurements add any further prognostic information regarding the future development of NMO.…”
Section: Figmentioning
confidence: 96%
“…After a single episode of ON, the VF tests were normal in only 2 of 36 eyes of patients with NMO compared with 17 of 35 eyes with MS (P = 0.001). 54 Another study reported a case of familial antiYaquaporin-4 antibodyYpositive NMO. Disease onset occurred at different ages, even within the same family.…”
Section: Optic Neuritis and Multiple Sclerosismentioning
confidence: 98%